2021
DOI: 10.1093/mnras/stab103
|View full text |Cite
|
Sign up to set email alerts
|

Optical and near-infrared observations of the SPT2349-56 proto-cluster core at z = 4.3

Abstract: We present Gemini-S and Spitzer-IRAC optical-through-near-IR observations in the field of the SPT2349-56 proto-cluster at z = 4.3. We detect optical/IR counterparts for only 9 of the 14 submillimetre galaxies (SMGs) previously identified by ALMA in the core of SPT2349-56. In addition, we detect four z ∼ 4 Lyman-break galaxies (LBGs) in the 30 arcsec-diameter region surrounding this proto-cluster core. Three of the four LBGs are new systems, while one appears to be a counterpart of one of the nine observed SMGs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 91 publications
7
42
0
Order By: Relevance
“…The velocity distribution and halo mass of the AzTEC14 group are similar to those of SPT234956, which is known as an extreme overdensity of SMGs at z = 4.3 (Miller et al 2018;Hill et al 2020). Rotermund et al (2021) shows that the stellar mass of the most massive member and total stellar mass of SPT234956 are at least -…”
Section: Size and Mass Evolutionmentioning
confidence: 68%
“…The velocity distribution and halo mass of the AzTEC14 group are similar to those of SPT234956, which is known as an extreme overdensity of SMGs at z = 4.3 (Miller et al 2018;Hill et al 2020). Rotermund et al (2021) shows that the stellar mass of the most massive member and total stellar mass of SPT234956 are at least -…”
Section: Size and Mass Evolutionmentioning
confidence: 68%
“…The Spitzer Space Telescope was used to observe SPT2349−56 at two wavelengths: 3.6 𝜇m (hereafter 'ch1') and 4.5 𝜇m (hereafter 'ch2'). A total of four observations have now been carried out since 2009, the first two of which were presented in Rotermund et al (2021), where further details can be found. The two subsequent observations used in this paper were carried out in January 2018 (proposal ID 13224, PI S. Chapman) and October 2019 (proposal ID 14216, PI S. Chapman), and uniformly covered ch1 and ch2 with 324 × 100 s dithered exposures (162 exposures per observation for each channel).…”
Section: Iracmentioning
confidence: 99%
“…The Gemini observations used in this paper were presented in Rotermund et al (2021), where details of the imaging, calibration, and data reduction can be found. Here we only provide a brief summary.…”
Section: Geminimentioning
confidence: 99%
See 2 more Smart Citations